Nanofibrous bio-inorganic hybrid structures formed through self-assembled peptide (FEFEFRFR): article / Marlina Nuraini Azmi, Dr Tan Huey Ling and Faiznur Mohd Fuad - Azmi, Marlina Nuraini; Tan, Dr Huey Ling; Mohd Fuad, Faiznur (2017)
The purpose of this research is to investigate the morphology of nanofibrous hybrid formed through self-assembled peptide (FEFEFRFR). It is also carried out to synthesize the HAp and characterize its properties of nanoparticles. HAp is used because of its crystallographic structure that commonly found in natural bond as an inorganic compounds with excellent biocompatibility, bioactivity and osteoconductivity. The peptide used is a sequence of Phenylalanine, Glutamic Acid and Arginine. This combination is made by considering the advantages of diversity in the body of amino acid residues to have a peptide with the special characteristics to be able to combine with HAp nanoparticles to form nanofibrous with large surface area and stronger structure. The methods to synthesize HAp known as precipitation method. The experimental work is carried out at first by synthesized of HAp before making it into supersaturated of HAp then the supersaturated HAp nanoparticles is mineralized with self-assembled peptide (FEFEFRFR). Then, the mineralized nanofibres is tuned by using three different media: distilled water, sodium perchlorate salt and sodium iodide salt. There are several equipment’s will be used to characterize the nanoparticles for the HAp nanoparticles without mineralization with peptides and with the mineralization with peptides namely Powder X-Ray Diffraction (XRD) to identify the phase of crystalline material which resulted in the high degree of the crystallinity, Fourier Transform Infrared Spectroscopy (FTIR) to characterize the functional group of HAp nanoparticles showed the most characteristic chemical groups which are PO₄³¯, OH-, and CO₃²¯, Inductive Coupling Plasma (ICP) to detect the presence of [Ca2+] ion with concentration of 4mM and Geology microscope to observe the surface morphology. The structure of elongated fibre is observed in distilled water, sodium perchlorate salt while amourphous structure in sodium iodide salt.